ANALYSIS OF THE EFFECT OF OIL PRICES ON PRICES OF PLASTIC SEED RAW MATERIALS - Maula Tri Wahyuni; Trias Marita Uswatun Chasanah; Risqy Maudy Inayah; Menur Kusumaningtyas (International Journal of Economic Integration and Regional Competitiveness, 2024)
This research aims to analyze how the price of petroleum influences the price of plastic pellet raw materials. The method used is linear regression analysis to evaluate the relationship between crude oil prices and plastic pellet raw material prices, taking into account other factors such as government policy and production efficiency. The research results show that there is a significant positive correlation between the price of petroleum and the price of plastic pellet raw materials. These findings emphasize the importance of effective risk management and purchasing strategies for companies in the plastics industry to deal with fluctuations in petroleum prices. This research can provide important insights for stakeholders in the plastics industry to optimize strategic and operational decisions.